Azerbaijan’s policy of destruction and appropriation of the cultural heritage of the Armenians of Artsakh in the context of violation of cultural rights - Tigranyan, Armine (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
The war unleashed by Azerbaijan against Artsakh on September 27, 2020, and the subsequent developments (the transfer of Artsakh’s historical territory under Azerbaijan’s control and the complete depopulation of Artsakh of its Armenian population) demonstrate that the systematic destruction of Armenian heritage has directly violated the cultural rights of the Armenians of Artsakh–depriving them of the ability to preserve and pass on their heritage to future generations. These destructions continue to this day on an alarming scale, deepening the crisis and erasing the Armenian presence in Artsakh. 2020 թ․ սեպտեմբերի 27-ին Արցախի դեմ Ադրբեջանի սանձազերծած պատերազմի, դրան հաջորդած գործընթացներում (պատմական հայկական տարածքի Ադրբեջանի վերահսկողության տակ անցնելն ու ամբողջական հայաթափումը) հայկական մշակութային ժառանգության ոչնչացումներն ուղղակիորեն խախտում են արցախահայերի մշակույթի իրավունքը՝ նրանց զրկելով պատմական մշակութային ժառանգության հետ հաղորդակցվելու, այն պատմական իսկությամբ պահպանելու, սերունդներին փոխանցելու հնարավորությունից։ Պատմական արժեքների ավերածությունները մեծ ծավալներով շարունակվում են մինչ օրս՝ ոչնչացնելով հայկական հետքն Արցախում։ Уничтожение армянского культурного наследия в ходе войны, развязанной Азербайджаном против Арцаха 27 сентября 2020 года, в последующих процессах (переход исторической армянской территории под контроль Азербайджана и полное насильственное переселение армян) напрямую нарушает культурные права армян Арцаха, лишая их возможности контактировать с историческим культурным наследием, сохранять его историческую подлинность и передавать его поколениям. Уничтожение исторических ценностей в больших масштабах продолжается по сей день, стирая армянский след в Арцахе.
Keywords: Cultural studies